Sedentary Lifestyle and Blood Glucose Regulation: A Physiological Perspective on Metabolic Imbalance - Hutapea, Albert Manggading; Marulitua Hutapea, Dwight Mahaputera (Oshada, 2025)
The increasing prevalence of sedentary behavior represents a global phenomenon that significantly contributes to the rising burden of metabolic disorders, particularly impaired blood glucose regulation. Glucose regulation is a central physiological mechanism in maintaining metabolic homeostasis, and its disruption has profound implications for cardiometabolic health. This study aims to synthesize scientific evidence on the relationship between sedentary lifestyle and blood glucose regulation from a physiological perspective, with a focus on the metabolic mechanisms underlying metabolic imbalance. A Systematic Literature Review with a qualitative synthesis approach was conducted using peer-reviewed journal articles published over the past ten years. A total of 22 eligible studies were analyzed through physiological thematic analysis and narrative synthesis. The findings indicate that sedentary behavior disrupts glucose regulation through reduced skeletal muscle activity, impaired GLUT-4 translocation, decreased insulin sensitivity, mitochondrial dysfunction, and increased adipose tissue inflammation. Over time, these alterations contribute to the progression of prediabetes, type 2 diabetes mellitus, and elevated cardiometabolic risk. This review highlights the critical role of physical activity in preserving metabolic balance and preventing glucose dysregulation